Healthcare services granted to patients with diagnosed acute initial or subsequent myocardial infarction in the Silesian voivodeship (Poland) - Choręza, Piotr; Filipecki, Artur; Kowalska, Małgorzata; Owczarek, Aleksander J. (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Cardiovascular diseases remains the leading cause of death in most of devoloped societies, including Poland. The study aimed to assess the changes in the number, duration, and costs of hospitalizations due to myocardial infarction in Silesian voivodeship (Poland) in 2009-2014. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Data were obtained from the Silesian Voivodeship Branch of the National Health Fund. The number, costs, and duration of healthcare services granted during an inpatient hospital stay to patients with acute initial or subsequent myocardial infarction in 2009-2014 were processed and analyzed quarterly for the whole Silesian voivodeship and its subregions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. From 54826 patients aged 66±12, the majority were males (62.3%) and 63.4% of 80866 hospitalizations were granted to them. We observed a decreasing trend for the total number of healthcare services granted in 2009-2014 that varied depending on the subregion. Simultaneously, we found that in most subregions the costs of services and the number of invasive services increased over time. We observed that treating patients above 80 years with acute initial or subsequent myocardial infarction generated lower costs of hospitalization but was extended in time. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Increased number and costs and accompanying reduced duration of hospitalizations granted in 2009-2014, especially in the range of invasive cardiology and cardiac surgery, results from implementing international guidelines and recommendations for acute myocardial infarction procedures. Lower cost and extended time of hospitalization for patients older than 80 years most likely result from using conservative (non-invasive) methods of treatment.